Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Synthesis and performance evaluation of cobalt-histidine hybrid nanoflowers as efficient heterogeneous catalysts for peroxymonosulfate activation - Qianqian Zhao; Huiyao Li; Junxue Chen; Fangui Meng; Lingfeng Deng; Kun Du (Journal of Environmental Chemical Engineering, 2025)

Strength and behavior of axially and eccentrically loaded built-up closed sections using four cold-formed steel open sections - Lingfeng Yin; Shaokuai Wang; Yongbiao Wang; Tianyang Deng; Zhanjie Li (Engineering Structures, 2024)

Mediation Effect of Body Mass Index on the Association of Urinary Nickel Exposure with Serum Lipid Profiles - Sibo Wang; Tiankai Shan; Jun Zhu; Qiqi Jiang; Lingfeng Gu; Jiateng Sun; Yulin Bao; Bo Deng; Hao Wang; Liansheng Wang (Biological Trace Element Research, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants - Xue Yin; Scott Jarvie; Wen‐Yong Guo; Tao Deng; Lingfeng Mao; Minhua Zhang; Chengjin Chu; Hong Qian; Jens‐Christian Svenning; Fangliang He (Global Ecology and Biogeography, 2021)
Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species within the EAS–ENA disjunct genera. Methods We compiled data on climate, species occurrence, growth form, and phylogeny to examine niche conservatism. We first built a phylogenetic tree to select intercontinental congeneric pairwise species and obtained their divergence times. We then quantified the observed niche overlaps with Schoener’s D , which has a 0–1 range, based on species occurrence and climate of species’ native ranges. To obtain projected distributions, each species’ niche was projected to the non‐native region using ensemble ecological niche models. Projected‐related niche overlaps were then calculated using projected distributions and the corresponding climatic conditions. Results Average observed niche overlaps of congeneric pairwise species were relatively small: .124, .211 and .109 for all, herbaceous and woody species, respectively. Both observed and projected‐related niche overlaps had significant negative relationships with divergence times of intercontinental congeneric pairwise species, with niche overlap for herbaceous species being higher than that for woody plants when controlling for divergence times. Main conclusions We conclude that the significant negative relationships between niche overlap and divergence times of congeneric pairwise species confirm niche conservatism among species of EAS–ENA disjunct plants and that the extent of niche conservatism is slightly different for herbaceous and woody plants. These findings suggest the potential role of allopatric speciation in EAS, and could help to understand the evolutionary history and the Asian‐bias diversity pattern of the EAS–ENA disjunct plants.

Regional disparity in extinction risk: Comparison of disjunct plant genera between eastern Asia and eastern North America - Houjuan Song; Alejandro Ordonez; Jens‐Christian Svenning; Hong Qian; Xue Yin; Lingfeng Mao; Tao Deng; Jian Zhang (Global Change Biology, 2021)
Climate and land cover changes are increasing threats to biodiversity globally. However, potentially varying biotic sensitivity is a major source of uncertainty for translating environmental changes to extinction risks. To reduce this uncertainty, we assessed how extinction risks will be affected by future human‐driven environmental changes, focusing on 554 species from 52 disjunct plant genera between eastern Asia (EAS) and eastern North America (ENA) to control for differences in environmental sensitivity at the genus level. Species distribution models were used to estimate and compare the vulnerability of species in disjunct genera between the two regions under two climate and land cover change scenarios (RCP2.6 and RCP8.5) in the 2070s, allowing to assess the effects of differences in climate and land cover pressures. Compared with ENA, stronger pressures from climate and land cover changes along with smaller range sizes in EAS translate into a larger number and proportion of species in disjunct genera becoming threatened by the 2070s. These regional differences are more pronounced under a best‐case climate scenario (RCP2.6), illustrating that strong climate change (RCP8.5) may override any regional buffer capacities. The main variables determining extinction risks differed between the two continental regions, with annual temperature range and cropland expansion being important in EAS, and annual precipitation being important in ENA. These results suggest that disparities in regional exposure to anthropogenic environmental changes may cause congeneric species with relatively similar sensitivity to have different future risks of extinction. Moreover, the findings highlight the context‐specific nature of anthropogenic effects on biodiversity and the importance of making region‐specific policies for conservation and restoration in response to the intensifying global changes.

Identification, evolution and expression analyses of Ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit gene family in wheat (Triticum aestivum L.) - Lingyue Qin; Yuanxia Xue; Ying Fei; Lingfeng Zeng; Shushen Yang; Xiping Deng (Acta Physiologiae Plantarum, 2018)